Increased Nuchal Translucency in Fetuses with Normal Karyotype - Anzhel, Simona; Kovachev, Emil; Zhekov, Zhivko; Georgiev, Boyan (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Increased nuchal translucency (NT) is associated with a high risk of chromosomal abnormalities and genetic syndromes. In fetuses with normal karyotype, thickened NT increases the likelihood of congenital heart malformations, spontaneous abortions, and stillbirths, especially in thickness > 3.5 mm. It was found that in the absence of accompanying structural abnormalities and a normal result of amniocentesis, the postnatal neurological development of the newborns did not differ from the general population. CASE PRESENTATION: The authors describe a case of sIUGR of monochorionic twins with second trimester selective umbilical cord ablation and livebirth of a healthy singleton. CONCLUSION: Abnormal NT thickness on early fetal morphology scan in euploid fetuses, especially in twin pregnancies, increase the suspicion for late complications of the pregnancy.